The Human Dimensions of Forest and Tree Health Global Perspectives (Springer International Publishing, 2018)
This book explores the specifically human dimensions of the problem posed by a new generation of invasive pests and pathogens to tree health worldwide. The growth in global trade and transportation in recent decades, along with climate change, is allowing invasive pests and pathogens to establish in new environments, with profound consequences for the ecosystem services provided by trees and forests, and impacts on human wellbeing. The central theme of the book is to consider the role that social science can play in better understanding the social, economic and environmental impacts of such tree disease and pest outbreaks. Contributions include explorations of how pest outbreaks are socially constructed, drawing on the historical, cultural, social and situated contexts of outbreaks; the governance and economics of tree health for informing policy and decision-making; stakeholder engagement and communication tools; along with more philosophical approaches that draw on environmental ethics to consider 'non-human' perspectives. Taken together the book makes theoretical, methodological and applied contributions to our understanding of this important subject area and encourages researchers from across the social sciences and humanities to bring their own disciplinary perspectives and expertise to address the complexity that is the human dimensions of forest and tree health. Chapter 5 and 11 are open access under a CC BY 4.0 license via link.springer.com. .